STUDY METHOD ON TIME AND MOTION OF SOLID WASTE COLLECTION AND TRANSPORTATION CASE STUDY IN 6 SITES OF HANOI - Chi, Ngô Kim; Tâm, Nguyễn Minh; Phượng, Đặng Ngọc (Vietnam Journal of Science and Technology, 2012)
SUMMARYOne method of time and motion study on solid waste collection and transportation was used in 6 investigated sites in Hanoi. Survey sheets have been designed and trained to carrying out study waste collection by hand push cart/waste bins along assigned routes and the load by trucks at the loading point in the streets, volume of collected waste, time of loading and transportation, time of each activity of waste collection. The results showed that; sweeping and picking up waste discharged in to the pavements was the most time consuming accounting for 60% of the total time. One waste collector collected an average of about 824kg/person/day, an average volume of 14.8tons/day colleted in Nguyen Du ward; average of 616kg/person/day and the amount of 11 tons/day collected in Phan Chu Trinh ward. The organic waste with about 20-25% of the total generated waste was separated from the normal – landfilled waste going to the Cau Dien composting plant by waste separation at source (WSS) in Phan Chu Trinh and Nguyen Du wards. In other sites without WSS such as Kim Giang, Me Tri, Nghi Tan, Dong Anh town, the volume of waste is 6,3 tons/day, 25,6 tons/day, 53,4 tons/day, 16,1 tons/day respectfully. One waste collector collected an average of 782, 640, 847, 503kg/person/day in Kim Giang, Me Tri, Nghia Tan, Đong Anh town. The results showed that the good habitude of discharging waste at regulated place and time should be maintained and encouraged in order to increase the effectiveness of the waste collection and transportation. The distribution of manpower as well as optimal the collection route and schedule should be done to increase the productivity of waste collection and transportation. The mentioned study method on time and motion of waste collection and transportation as well as its use will create an effective tool and permit to carry out quantitatively the solid waste collection and transportation in Hanoi with the specific characteristics of narrow routes. It is need to detailed and technical document this study method in order to create one useful tool and technical method to investigate municipal solid waste management in Vietnam.